Exploration of the Influence of TikTok Live Streaming on Increasing Consumer Purchase Interest - Poppy Wulandari; Sabrina Azra; Siti Aisyah Buana; Aurel Chesya Putri Masayu; Eurosey Caroline Br. Panjaitan (Bina Nusantara University, 2025)
The development of digital platforms has made social media an important marketing tool that plays a crucial role in the success of a business. One of the features that attracts consumers is TikTok live streaming, which enables real-time interaction between sellers and buyers online. This study aims to analyze the impact of TikTok live streaming on increasing consumer purchase intention. Using a qualitative method, the research collects data through interviews conducted with active users of TikTok live streaming, as well as an analysis of the content created by sellers. The results of this study reveal several key factors that influence consumer purchase intention, namely real-time communication conducted by the seller, delivery speed, and ease of obtaining discounts and attractive promotions. Respondents are interested in shopping during live streaming due to several main factors, such as the seller's interactive communication style, clearer product displays thanks to live demonstrations, and the sense of urgency created by exclusive promotions and limited stock. Additionally, trust in the seller also increases through real-time interactions, where consumers can ask questions and receive immediate answers before making a purchase decision. This research provides valuable insights for business owners on strategies that can be implemented in live streaming, particularly in building audience engagement and encouraging purchase decisions more effectively.